Product Innovation and National Image of Chinese Products in the Eyes of Thai People - Qiuxue Luo; Mayuree Suacamram (SAGE Open, 2022)
This paper developed products from Guangxi, China, for customers in Bangkok, Thailand, and investigates the influence of country image and product innovation on purchasing eight products: a tea shop, flower tea, traditional Chinese dress, Chinese language lessons, an instant hotpot, Chinese noodles, jujube, and Chinese jewelry. The study followed four steps: (1) researching the demand of product development from documents and interviews with Chinese entrepreneurs; (2) developing a product concept and presenting it to two business experts; (3) selecting five products with the highest expert ratings and conducting a survey to collect data about the products from Thai customers; and (4) analyzing the level of buying decisions and influence of product country image and product innovation on each of the five products. Content analysis, path analysis, and multigroup techniques were used for data analysis. Results revealed that products with a high level of product innovation and buying decisions that introduced technology provided better value and that product innovation influenced buying decisions in all product categories. Product country image, however, only influenced buying decisions for Chinese jewelry and Chinese language lessons. JEL Classification: M01, M03